Aspek Hukum Pengelolaan Transportasi Umum Berbasis Aplikasi Online Menurut Undang-Undang Pengangkutan - Efendy; Doni Defriansyah; Eka wijaya; Edi Haryadi (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
The development of online app-based public transportation in Indonesia has brought about significant changes in people's mobility patterns by offering easier access, efficient services, and high flexibility. While providing many benefits, this innovation also presents legal challenges, particularly regarding the responsibility of app providers and consumer protection. Through a normative legal approach, this article asserts that app providers cannot be viewed solely as technology facilitators but must also be regarded as business entities obligated to adhere to principles of safety, comfort, and consumer protection as stipulated in the Transportation Act. Additionally, the urgency of harmonizing regulations between the transportation and digital technology sectors is crucial to avoid overlapping authorities and ensure legal certainty. Therefore, the management of online transportation must be based on a balance between technological innovation and the protection of public interests, to achieve a fair, sustainable transportation system that aligns with national legal mandates.